Mercury Safety Reform in the 21st Century: Advancing the New Framework for Toxic Substances Control. Issue 4 (4th July 2017) - Ogunseitan, Oladele A.
Abstract : The articles that follow are the latest in Environment Magazine's series looking back at seminal articles in the magazine's history that helped define a field of study or offered alternative explorations of new ideas. In this installment, we focus on the latest news in the hazards of the mercury toxin, juxtaposed with Environment 's groundbreaking article on mercury published in 1969.